Short-Period Internal Waves under an Ice Cover in Van Mijen Fjord, Svalbard - E. G. Morozov; S. V. Muzylev; A. S. Shestov; A. V. Marchenko (Advances in Meteorology)
Temperature and velocity fluctuations measured in Van Mijen Fjord in Svalbard and interpreted as the fluctuations induced by internal waves revealed the existence of short-period internal waves with an amplitude of approximately 1 m and a period of approximately 5–10 min that correlate with the ice cover fluctuations of the same period with an amplitude of a few millimeters.